2020
DOI: 10.1111/jch.14005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical benefits and safety of renal denervation in severe arterial hypertension: A long‐term follow‐up study

Abstract: Funding information TFL has received research grants from Boston Scientific and St. Jude Medical and consulting honoraria from Medtronic and St. Jude Medical. IS and AJF received lecture honoraria from Medtronic. FR reports grant support for the ESC-HFA Postgraduate Course in Heart Failure from Novartis, Servier, Bayer, Abbott and Astra Zeneca and the VASCEND trial from Novartis (all payments directly to the University of Zurich). FR has been paid for the time spent as a committee member for clinical trials, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, when assessed immediately after intervention (1 min), RDN was showed to be effective in reducing HRV [58]. There are also studies that did not show any significant effect of RDN on HR [59]. However, most of these studies suffer from some limitations, such as low patient numbers, lack of control group, lack of sham procedure, great number patients included under treatment of beta blockers, to name just few.…”
Section: Heart Ratementioning
confidence: 99%
“…However, when assessed immediately after intervention (1 min), RDN was showed to be effective in reducing HRV [58]. There are also studies that did not show any significant effect of RDN on HR [59]. However, most of these studies suffer from some limitations, such as low patient numbers, lack of control group, lack of sham procedure, great number patients included under treatment of beta blockers, to name just few.…”
Section: Heart Ratementioning
confidence: 99%
“…Data showed that DBP and SBP levels were significantly lower at 24 months after RDN, and neither the recovery of nerve fibers nor the effective counter-regulatory mechanism that elevates BP was found [39]. Even 36 months after RDN, BP was significantly lower than before RDN [40].…”
Section: Discussionmentioning
confidence: 90%
“…It might lower blood pressure by reversing these mechanisms. Clinical trials [14][15][16][17][18] showed that RDN can effectively reduce intractable blood pressure in hypertensive patients. This study is a prospective, randomized controlled study, and the results also show that RDN can significantly reduce patient blood pressure.…”
Section: Discussionmentioning
confidence: 99%